Modulation by Sigma-1 Receptor of Morphine Analgesia and Tolerance: Nociceptive Pain, Tactile Allodynia and Grip Strength Deficits During Joint Inflammation - Montilla-García, Ángeles; Tejada, Miguel Á.; Ruiz-Cantero, M. Carmen; Bravo-Caparrós, Inmaculada; Yeste, Sandra; Zamanillo, Daniel; Cobos, Enrique J. (Frontiers in Pharmacology, 2019)
Sigma-1 receptor antagonism increases the effects of morphine on nociceptive pain, even in morphine-tolerant animals. However, it is unknown whether these receptors are able to modulate morphine antinociception and tolerance during inflammatory pain. Here we used a mouse model to test the modulation of morphine effects by the selective sigma-1 antagonist S1RA (MR309), by determining its effect on inflammatory tactile allodynia (von Frey filaments) and on grip strength deficits induced by joint inflammation (a measure of pain-induced functional disability), and compared the results with those for nociceptive heat pain recorded with the unilateral hot plate (55 °C) test. The subcutaneous (s.c.) administration of morphine induced antinociceptive effects to heat stimuli, and restored mechanical threshold and grip strength in mice with periarticular inflammation induced by Complete Freund’s Adjuvant. S1RA (80 mg/kg, s.c.) administered alone did not induce any effect on nociceptive heat pain or inflammatory allodynia, but was able to partially reverse grip strength deficits. The association of S1RA with morphine, at doses inducing little or no analgesic-like effects when administered alone, resulted in a marked antinociceptive effect to heat stimuli and complete reversion of inflammatory tactile allodynia. However, S1RA administration did not increase the effect of morphine on grip strength deficits induced by joint inflammation. When S1RA (80 mg/kg, s.c.) was administered to morphine-tolerant animals, it rescued the analgesic-like effects of this opioid in all three pain measures. However, when S1RA was repeatedly given during the induction of morphine tolerance (and not on the day of behavioral evaluation) it failed to affect tolerance to the effects of morphine on nociceptive heat pain or inflammatory allodynia, but completely preserved the effects of this opioid on grip strength deficits. These effects of S1RA on morphine tolerance cannot be explained by pharmacokinetic interactions, given that the administration of S1RA did not modify concentrations of morphine or morphine-3-glucuronide (a major morphine metabolite) in morphine-tolerant animals in plasma or brain tissue. We conclude that sigma-1 receptors play a pivotal role in the control of morphine analgesia and tolerance in nociceptive and inflammatory pain, although in a manner dependent on the type of painful stimulus explored.